Chronic vs. Acute Interactions between Supraoptic Oxytocin Neurons and Astrocytes during Lactation: Role of Glial Fibrillary Acidic Protein Plasticity - Yu-Feng Wang; Kathryn A. Hamilton (The Scientific World Journal)
In this article, we review studies of astrocytic-neuronal interactions and their effects on the activity of oxytocin (OXT) neurons within the magnocellular hypothalamo-neurohypophysial system. Previous work over several decades has shown that withdrawal of astrocyte processes increases OXT neuron excitability in the hypothalamic supraoptic nucleus (SON) during lactation. However, chronically disabling astrocyte withdrawal does not significantly affect the functioning of OXT neurons during suckling. Nevertheless, acute changes in a cytoskeletal element of astrocytes, glial fibrillary acidic protein (GFAP), occur in concert with changes in OXT neuronal activity during suckling. Here, we compare these changes in GFAP and related proteins with chronic changes that persist throughout lactation. During lactation, a decrease in GFAP levels accompanies retraction of astrocyte processes surrounding OXT neurons in the SON, resulting from high extracellular levels of OXT. During the initial stage of suckling, acute increases in OXT levels further strengthen this GFAP reduction and facilitate the retraction of astrocyte processes. This change, in turn, facilitates burst discharges of OXT neurons and leads to a transient increase in excitatory neurochemicals. This transient neurochemical surge acts to reverse GFAP expression and results in postburst inhibition of OXT neurons. The acute changes in astrocyte GFAP levels seen during suckling likely recur periodically, accompanied by rhythmic changes in glutamate metabolism, water transport, gliotransmitter release, and spatial relationships between astrocytes and OXT neurons. In the neurohypophysis, astrocyte retraction and reversal with accompanying GFAP plasticity also likely occur during lactation and suckling, which facilitates OXT release coordinated with its action in the SON. These studies of the dynamic interactions that occur between astrocytes and OXT neurons mediated by GFAP extend our understanding of astrocyte functions within the central nervous system.